Fisioterapia respiratoria na pressao intracraniana de pacientes graves internados em unidade de terapia intensiva: revisao sistematica - Ferreira, Lucas Lima; Valenti, Vitor Engracia; Vanderlei, Luiz Carlos Marques (Associação de Medicina Intensiva Brasileira - AMIB, 2013)
Objetivo: Analisar os desfechos aumento/diminuição da pressão intracraniana e/ou queda da pressão de perfusão cerebral, proporcionados pela fisioterapia respiratória em pacientes graves assistidos em unidade de terapia intensiva. Métodos: Por meio de uma revisão sistemática da literatura, foram selecionados ensaios clínicos publicados entre 2002 e 2012. A busca envolveu as bases de dados LILACS, SciELO, MedLine e PEDro, usando os descritores physical therapy, physiotherapy, respiratory therapy e randomized controlled trials em cruzamento com o descritor intracranial pressure. Resultados: Foram incluídos 5 estudos, que somaram 164 pacientes, com média de idade entre 25 e 65 anos, e que indicaram que as manobras de fisioterapia respiratória aumentaram significativamente a pressão intracraniana, sem alterar a pressão de perfusão cerebral. Os artigos abordaram as técnicas de vibração, vibrocompressão, tapotagem, drenagem postural, além da manobra de aspiração intratraqueal. Todos os pacientes estavam sob ventilação mecânica invasiva. Conclusão: A fisioterapia respiratória promove aumento da pressão intracraniana. Os estudos sugerem que não há repercussões hemodinâmicas e respiratórias a curto prazo ou alteração da pressão de perfusão cerebral. Entretanto, não há estudos que avaliem desfechos clínicos e que assegurem a segurança das manobras.

Objective: To analyze the outcomes of increased or decreased intracranial pressure and/or the decrease in cerebral perfusion pressure resulting from respiratory physiotherapy on critically ill patients admitted to the intensive care unit. Methods: Through a systematic review of the literature, clinical trials published between 2002 and 2012 were selected. The search involved the LILACS, SciELO, MedLine and PEDro databases using the keywords physical therapy, physiotherapy, respiratory therapy and randomized controlled trials combined with the keyword intracranial pressure. Results: In total, five studies, including a total of 164 patients between 25 and 65 years of age, reporting that respiratory physiotherapy maneuvers significantly increased intracranial pressure without changing the cerebral perfusion pressure were included. The articles addressed several techniques including vibration, vibrocompression, tapping, postural drainage, and the endotracheal aspiration maneuver. All patients required invasive mechanical ventilation. Conclusion: Respiratory physiotherapy leads to increased intracranial pressure. Studies suggest that there are no short-term hemodynamic or respiratory repercussions or changes in the cerebral perfusion pressure. However, none of the studies evaluated the clinical outcomes or ensured the safety of the maneuvers.
Chest physiotherapy on intracranial pressure of critically ill patients admitted to the intensive care unit: a systematic review
Keywords: Modalidades de fisioterapia; Pressao intracraniana; Cuidados criticos; Terapia respiratoria; Physical therapy modalities; Intracranial pressure; Critical care; Respiratory physiotherapy